2022
DOI: 10.14309/ctg.0000000000000490
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab vs Infliximab in Pediatric Patients With Crohn's Disease: A Propensity Score Analysis and Predictors of Treatment Escalation

Abstract: INTRODUCTION:Two antitumor necrosis factor therapies (infliximab [IFX] and adalimumab [ADA]) have been approved for the treatment of pediatric Crohn's disease (CD) but have not been compared in head-to-head trials. The aim of this study was to compare the efficacy and safety of ADA and IFX by propensity score matching in a prospective cohort of pediatric patients with luminal CD and at least a 24-month follow-up.METHODS:Among 100 patients, 75 met the inclusion criteria, and 62 were matched by propensity score.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
1
2
0
Order By: Relevance
“…Limited comparative effectiveness studies exist in children to date. Our results build on a recent comparative effectiveness study in children with CD that showed no difference in primary nonresponse between those treated with ADA or IFX (10). Our results also seem to be consistent with noncomparative pediatric studies.…”
Section: Discussionsupporting
confidence: 89%
“…Limited comparative effectiveness studies exist in children to date. Our results build on a recent comparative effectiveness study in children with CD that showed no difference in primary nonresponse between those treated with ADA or IFX (10). Our results also seem to be consistent with noncomparative pediatric studies.…”
Section: Discussionsupporting
confidence: 89%
“…The discontinuation rate was 3.2% per year due to a loss of response in a Canadian study [ 11 ]. Treatment outcomes suggest that patients with high disease activity in Crohn’s disease respond equally well to infliximab and adalimumab, although randomized controlled head-to-head studies are lacking [ 12 , 13 ]. After three months of treatment, infliximab induced significant mucosal healing and was associated with improvement in clinical disease scores in adults [ 14 ].…”
Section: Clinical Effect Of Biologicsmentioning
confidence: 99%
“…A randomized clinical trial comparing the efficacy of infliximab to adalimumab in patients with IBD has not been performed, though several observational studies showed comparable efficacy in adults (13,14). Similar analyses comparing pediatric patients with CD or UC, treated with infliximab and adalimumab, showed comparable efficacy and safety (15)(16)(17)(18)(19). However, a retrospective study showed that in UC, adalimumab was less likely to induce mucosal healing when compared to infliximab (20).…”
mentioning
confidence: 99%